(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The paper presents a mixed-methods approach to investigate and assess the design of the public realm in Sharjah’s old town or "the Heart of Sharjah", a regenerated and restored urban center, and to understand the features that contribute to a well-designed public realm in this specific context. A literature review is conducted to gather insights and identify key qualitative and physical features associated with user satisfaction and social engagement in public spaces. The physical features include diverse seating, shade greenery, water surfaces, landmarks, play zones, and economic activities. Similarly, various qualitative features were recognized including accessibility, adaptability, public participation, environmental sustainability, safety, and the creation of a sense of place. The current status of the public realm in the study area is later assessed using mapping and land-use analysis, utilizing Google Earth maps and on-site photographs for visual documentation. The identified features are used as evaluation criteria, and a systematic assessment of the design is conducted, highlighting areas where improvements are needed. Based on the evaluation results, recommendations are formulated to enhance the urban space and address the identified shortcomings, aiming to improve user satisfaction and promote social engagement. The evaluation findings indicate that the area lacks pedestrian accessibility, shading, various amenities, green areas water surfaces, and public engagement in design and management. This research contributes to the understanding of designing inclusive and vibrant public realms in historic urban contexts, providing valuable insights for urban planners and policymakers.